A proton-conductive antifreeze organic hydrogel electrolyte and a preparation method thereof
PolyAH-E hydrogel electrolyte is prepared by randomly copolyping acrylamide and anionic monomers in a mixed solution of ethylene glycol and water, which solves the problem of freezing of traditional hydrogel electrolytes at low temperatures, and achieves good maintenance of high ionic conductivity and mechanical properties. It is suitable for flexible supercapacitors.
Patent Information
- Application Number
- CN202211552551.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-05
AI Technical Summary
Traditional hydrogel electrolytes freeze at low temperatures, resulting in significant weakening or loss of ionic conductivity and mechanical flexibility, limiting the application of flexible supercapacitors at low temperatures.
PolyAH-E hydrogel electrolyte was prepared by randomly copolyacrylamide (AM) and anionic monomer 2-acrylamide-2-methyl-1-propane sulfonic acid (AMPS) in a mixed solution of ethylene glycol and water, and the monomer ratio and EG content were regulated to achieve good low-temperature performance.
PolyAH-E hydrogel electrolyte maintains high ionic conductivity and excellent tensile strain and tensile stress at low temperatures. It has extremely strong plasticity and excellent water retention ability, and is suitable for flexible supercapacitors.
Smart Images

Figure CN116082665B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials and relates to the research of surface functional materials, and specifically to the preparation, properties and application of single proton conductive antifreeze organic hydrogel. Background Art
[0002] With the rapid development of society, the global demand for new technologies and new energy sources has increased rapidly, which has also prompted the emergence of new materials and energy storage devices. Miniaturized and portable flexible wearable electronic devices have brought about explosive development. Among them, as an electronic energy storage device, flexible supercapacitors (SC) have attracted much attention due to their advantages such as light weight, high power density, fast charging and discharging capabilities, and mechanical flexibility. Hydrogels are widely regarded as ideal materials for flexibility (SC) due to their inherent conductivity, good mechanical properties, and biocompatibility. However, the large amount of water contained in traditional hydrogel electrolytes will inevitably freeze below 0°C. This causes the ionic conductivity and mechanical flexibility of the electrolyte to be significantly weakened or even lost. This severely limits the application of SC at low temperatures.
[0003] There are now a large number of reports on solving the problem of hydrogel freezing at low temperatures. For example, Suo et al. can lower the freezing point of the hydrogel system to -57°C by 30wt% CaCl2. However, 10wt% CaCl2 can only lower the freezing point of the hydrogel system to -7°C (XPMorelle, WR Illeperuma, K. Tian, R. Bai, Z. Suo, JJ Vlassak, Adv. Mater. 2018, 30, 1801541). The antifreeze hydrogel prepared by Wang et al. using 3M LiTFSI has a conductivity of only 0.1mS cm-1 at -40°C (ChemSusChem 2021, 14, 2056–2066). However, the introduction of a large amount of inorganic salts is bound to lead to an increase in cost. At the same time, excessively high salt concentrations will corrode the energy storage device and cause safety hazards.
[0004] Some people have also tried to prepare polymers by in-situ polymerization in a nitrogen or rare gas atmosphere using polymerizing monomers including acrylamide, acrylic acid, hydroxyethyl methacrylate, 2-acrylamido-2-methyl-1-propane sulfonic acid, polyethylene glycol (diol) diacrylate, 2-methacryloyloxyethyl phosphorylcholine, methacryloylethyl sulfobetaine, 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, etc., using oxygen plasma to activate the substrate; however, the process is very complicated, the cost is high, and a good antifreeze effect cannot be achieved at low temperatures. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method of a PolyAH-E hydrogel electrolyte and its use as a single-electron conductive antifreeze hydrogel electrolyte in view of the deficiencies of the prior art. The preparation method is simple and can be used to prepare a series of antifreeze hydrogel electrolytes. The antifreeze hydrogel electrolyte still has high conductivity, excellent tensile strain and tensile stress at low temperatures.
[0006] The technical solution of the present invention is as follows:
[0007] A PolyAH-E hydrogel, characterized in that the hydrogel is obtained by random polymerization of monomer acrylamide (AM) and anionic monomer 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS) in a mixed solution of ethylene glycol (EG) and water, wherein in the polymerization unit, the molar ratio of AM and AMPS monomers is (6:1) to (1:6), and the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 0% to 70%.
[0008] Preferably, in the PolyAH-E hydrogel, the ratio of monomer mass to mixed solution volume is 1:2 to 1:4. The total mass of AM and AMPS monomers is referred to as monomer mass.
[0009] Preferably, the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 0% to 70%. Preferably, the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 10% to 70%; more preferably, the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 30% to 70%.
[0010] Preferably, the freezing point of the hydrogel electrolyte is lower than -21.62°C.
[0011] Preferably, when the EG volume ratio is 0 and the AM:AMPS ratio is (6:1) to (1:6), the ionic conductivity of the polyAH hydrogel electrolyte is 82.89 to 230.09 mS cm -1 Preferably, when the ratio of AM:AMPS is 3:1 to 1:3, the ionic conductivity of the polyAH hydrogel electrolyte is 137.81 to 211.94 mS cm -1 .
[0012] When AM:AMPS is 3:1 to 1:3 and the EG volume ratio is 0, the stress of the polyAH hydrogel electrolyte is 48.9 to 11.3 kPa and the strain is 376.36% to 480.02%.
[0013] Preferably, at room temperature, when the volume ratio of EG is 30% to 70%, the stress of the polyAH hydrogel electrolyte is 37.3 to 11.7 kPa, and the strain is 728.92% to 1772.72%.
[0014] Preferably, at -40°C, when the EG volume ratio is 30% to 70%, the ionic conductivity of the polyAH hydrogel electrolyte is 0.55 to 1.28 mS cm -1 .
[0015] After 8 days, the water retention capacity of polyAH electrolyte with ethylene glycol content of 30% to 70% is 50% to 90%.
[0016] The present invention also provides a method for preparing the above-mentioned PolyAH-E hydrogel electrolyte, comprising the following steps:
[0017] S1, dissolving AM and AMPS monomers in an ethylene glycol aqueous solution, wherein the molar ratio of AM and AMPS monomers is (6:1) to (1:6), the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 0% to 70%, and the ratio of the monomer mass to the mixed solution volume is 1:2 to 1:4.
[0018] S2, place the solution obtained in S1 in an ice bath and stir for 0.5 to 1.5 hours until all the monomers are dissolved.
[0019] S3, adding an initiator to the solution obtained in S2, stirring in an ice bath for 20 to 40 minutes, and ultrasonically shaking for 5 to 15 minutes to remove bubbles, to obtain a precursor solution. The initiator is APS, and the amount of the initiator added is 0.5 to 1.5 wt% of the monomer mass;
[0020] S4, injecting the precursor solution into the mold, sealing it and placing it in an environment of 30 to 50° C. for polymerization for 8 to 16 hours.
[0021] The hydrogel obtained by polymerization is abbreviated as polyAxHy-Ez, where x and y are the molar ratios of AM and AMPS, respectively, and z is the volume concentration of EG.
[0022] Preferably, in step S1, the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 10% to 70%; more preferably, the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 30% to 70%. AM and AMPS monomers are dissolved separately and then mixed, or AM and AMPS monomers are mixed first and then put into the solvent. Both methods will not affect the results, because both monomers are hydrophilic monomers and will not affect the solubility of the other monomer, and no initiator is added in this step, so there will be no premature reaction.
[0023] Preferably, in step S2, the solution obtained in S1 is placed in an ice bath and stirred for 0.8 to 1.2 hours.
[0024] Preferably, in step S3, more preferably, the amount of the initiator added is 1 wt% of the monomer mass.
[0025] The present invention has the following beneficial effects:
[0026] The polyAH-E electrolyte has excellent low temperature performance. By adjusting the monomer ratio and EG content, it was found that when AM:AMPS=3:1 and the EG content was 50vol%, that is, polyA3H1-E 50 The electrolyte has the best comprehensive performance. 50 The tensile strain and tensile stress of the electrolyte are 1058.6% and 28.6 kPa, respectively. polyA3H1-E 50 The electrolyte can still provide 1.28mS cm at -40℃ -1 High ionic conductivity.
[0027] polyA3H1-E 50 The electrolyte has strong plasticity and can be molded into different shapes according to different needs. It can be molded into different shapes according to different needs. At the same time, it has excellent water retention ability. When the electrolyte is placed in a dry environment for eight days, it can still retain 78.94% of its initial mass.
[0028] The present invention dissolves a hydrophilic monomer acrylamide (AM) and an anionic monomer 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS) in a water / ethylene glycol binary solvent, and prepares a series of antifreeze hydrogel electrolytes (polyAH-E electrolytes) by a one-pot method. The preparation method is simple and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the preparation of antifreeze hydrogel;
[0030] Figure 2 Photos of gels formed after polymerization of monomer combinations with different molar ratios;
[0031] Figure 3 Ionic conductivity of hydrogel electrolytes with different monomer molar ratios;
[0032] Figure 4 Stress-strain curves of hydrogel electrolytes with different monomer molar ratios;
[0033] Figure 5 Stress-strain curves of hydrogel electrolytes with different EG contents;
[0034] Figure 6 Temperature dependence of ionic conductivity of different electrolytes;
[0035] Figure 7The electrostatic interactions (b) formed between anions and cations (a) inside the electrolyte allow for free transport under applied voltage;
[0036] Figure 8 polyA3H1-E0 and polyA3H1-E 50 Photographs of the electrolyte at room temperature and -40°C;
[0037] Fig. 9 The relationship between the number of days of exposure to air and the mass loss of the specimen;
[0038] Fig.10 DSC curves of hydrogel electrolytes with different EG contents;
[0039] Fig.11 Electron microscope image of SC;
[0040] Fig.12 Voltage window of the assembled SC;
[0041] Fig.13 CV curves of SC at different scan rates at (a) 25°C and (c) 60°C; GCD curves at different current densities at (b) 25°C and (d) 60°C.
[0042] Fig.14 CV, GCD and EIS curves of SC at different temperatures;
[0043] Fig.15 (a) CV curves of SC at different scan rates and (b) GCD curves of SC at different current densities at -40 °C.
[0044] Fig.16 (a) CV, (b) GCD, and (c) EIS curves of two SCs connected in series and in parallel. DETAILED DESCRIPTION
[0045] The following examples are provided to further illustrate the present invention, but the present invention is not limited thereto.
[0046] Materials and reagents
[0047] 2-Acrylamido-2-methyl-1-propanesulfonic acid (C7H 13 NO4S), analytical grade, Aladdin Reagent Co., Ltd.; acrylamide (C3H5NO), analytical grade, Aladdin Reagent Co., Ltd.; ammonium persulfate ((NH4)2S2O8), analytical grade, Aladdin Reagent Co., Ltd.; N,N-methylenebisacrylamide (C7H 10N2O2), analytical grade, Aladdin Reagent Co., Ltd.; ethylene glycol ((CH2OH)2), analytical grade, Sinopharm Chemical Reagent Co., Ltd.; polyvinylidene fluoride ([CH2CF2]n), analytical grade, Macklin Biochemical Technology Co., Ltd.; N-methylpyrrolidone (C5H9NO), analytical grade, Macklin Biochemical Technology Co., Ltd.; carbon cloth, W0S1011, CeTech Co., Ltd., Taiwan, China; activated carbon, YP-50F, Kuraray Co., Ltd., Japan; carbon black, battery grade, Alfa Aesar Co., Ltd.
[0048] Experimental instruments and equipment
[0049] Constant temperature blast oven, DHG-9123A, Shanghai Yiheng Scientific Instrument Co., Ltd.; ultrasonic cleaner, KQ3200B, Kunshan Ultrasonic Instrument Co., Ltd.; microcomputer-controlled universal mechanical testing machine, WDW-02, Jinan Hengsi Shengda Instrument Co., Ltd.; heat-collecting constant temperature magnetic stirrer, DF-101S, Henan Yuhua Instrument Co., Ltd.; constant temperature and humidity test chamber, LS-TH-100S, Rice Testing Equipment Co., Ltd.; differential scanning calorimeter, TAQ-10, TA Company, USA; electrochemical workstation, CHI660E, Shanghai Chenhua Instrument Co., Ltd.; laser confocal Raman spectrometer, Lab RAM H600, HORIBAJY Company, France.
[0050] Test Characterization
[0051] Mechanical properties test
[0052] Mechanical measurements were performed using a universal mechanical testing instrument (Hensgrand, WDW-02, China). -1 The tensile speed is to stretch a cylinder with a diameter of 6mm and a length of 40mm. The mechanical properties test is carried out by multiple measurements, and the median data is taken for analysis in the data set with the most results.
[0053] Water retention test of organic hydrogel electrolyte
[0054] Take two pieces of polyA3H1-E0 and polyA3H1-E of equal mass. 50 The gel electrolyte was exposed to air at room temperature, and its mass was recorded every 24 hours.
[0055] Electrochemical Performance Measurement of PolyAH-E Organic Hydrogel Electrolyte
[0056] The ionic conductivity (σ) of the hydrogel electrolyte was measured using a dual-probe method on a CHI 660E electrochemical workstation. The amphoteric hydrogel electrolyte was filled in a CR927 battery case and stabilized at different temperatures for 1 to 2 hours, and then the conductivity was measured at the corresponding temperature. Each group of samples was measured 3 to 5 times and the average value was taken. The ionic conductivity was calculated according to the formula.
[0057]
[0058] Where R is the resistance (Ω), S is the cross-sectional area of the electrolyte being measured (cm 2 ), L is the thickness of the sample being tested (cm).
[0059] Cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and constant current charge-discharge (GCD) measurements were performed using a two-electrode system on a CHI660E workstation. CV was performed at different scan rates between 0 and 1 V. EIS was performed at 10 mV amplitude between 0.01 Hz and 100 kHz. GCD was performed at different current densities between 0 and 1 V. The mass specific capacitance (Csp, F g -1 ) is obtained from the discharge curve of GCD and calculated according to the following formula.
[0060]
[0061] Where I is the discharge current (mA), Δt is the discharge time (s), m device is the total mass of the two electrodes of the supercapacitor (g), and ΔV represents the discharge voltage (V).
[0062] Other tests
[0063] Differential scanning calorimetry (DSC) was performed using a TA2500 instrument. The sample was first cooled from room temperature to -80 °C, and then heated from -80 °C to 60 °C. The cooling and heating rates were both 15 °C min -1 The sample mass is between 5-10 mg. The sample test is carried out under the protection of nitrogen environment.
[0064] Example 1 Preparation of PolyAH-E hydrogel
[0065] A series of polyAH-EG organohydrogels were obtained by random copolymerization of AM and AMPS in a mixed solution of ethylene glycol (EG) and water. The preparation process of polyAH-E hydrogel is as follows: Figure 1As shown. First, AM and AMPS monomers (total mass of 2.0 g) were dissolved in ethylene glycol aqueous solution (4.0 mL) of different volume concentrations. Then, the above solution was placed in an ice bath and stirred for 1 hour. After all the monomers were dissolved, 0.02 g of initiator (APS, 1 wt% of the monomer mass) was added to the mixed solution, stirred in an ice bath for 0.5 h, and ultrasonically vibrated for 10 min to remove bubbles. The precursor solution was then injected into the mold, sealed and placed in a 40°C environment for polymerization for 12 hours. The hydrogel obtained by polymerization is abbreviated as polyAxHy-Ez, where x and y are the molar ratios of AM and AMPS, respectively, and z is the volume concentration of EG.
[0066] Example 2
[0067] The rest is the same as in Example 1, except that:
[0068] The EG concentration was 0, and the molar ratio of AM and AMPS was changed. The ratios of AM:AMPS = 6:1, 3:1, 1:1, 1:3, and 1:6 were used respectively, and it was found that all monomer ratios had good ability to form solid gels. Figure 2 As shown, hydrogels with different monomer ratios were polymerized at 40°C for 12 hours, and then the glass bottles containing hydrogels with different monomer ratios were inverted. Obviously, the polymerized hydrogels with different monomer ratios were all at the bottom of the bottle and did not flow down due to inversion, which shows that hydrogels with all monomer ratios were successfully polymerized and all had good solid-state properties.
[0069] Acrylamide (AM) has both hydrogen bond donors and hydrogen bond acceptors inside, and its polymerization conditions are simple, making it an excellent material that is very suitable for preparing hydrogels. 2-Acrylamido-2-methyl-1-propanesulfonic acid (AMPS) is a strong organic acid that can easily dissociate the protons it carries. Introducing AMPS into the hydrogel can bring high ionic conductivity to the hydrogel. In this work, we used the hydrophilic monomer AM and the anionic monomer AMPS to construct a hydrogel with high ionic conductivity. Ethylene glycol (EG) provides a guarantee for the antifreeze property of the hydrogel. It is added by mixing with water before the polymerization of the hydrogel. Subsequently, the antifreeze hydrogel polyAH-E was prepared by a one-pot method.
[0070] Example 3 Mechanical properties and ionic conductivity of electrolyte
[0071] Ionic conductivity is one of the most important indicators of electrolytes. By testing the conductivity of hydrogel electrolytes with different monomer ratios at room temperature, it is found that there are huge differences in the conductivity of hydrogels with different monomer ratios. Figure 3As shown in Figure 2, AMPS is the conductive medium of polyAH hydrogel electrolytes. Its content directly determines the ionic conductivity of polyAH hydrogel electrolytes. For example, the ionic conductivity of polyA1H6 hydrogel electrolytes with high AMPS content is as high as 230.09 mS cm -1 However, when the content of AMPS was reduced to a molar ratio of 6:1 (AM:AMPS), the ionic conductivity of polyA6H1 dropped sharply to 82.89 mS cm -1 When AM:AMPS is (6:1) to (1:6), the ionic conductivity of polyAH hydrogel electrolyte is 82.89 to 230.09 mS cm -1 Preferably, when the ratio of AM:AMPS is 3:1 to 1:3, the ionic conductivity of the polyAH hydrogel electrolyte is 137.81 to 211.94 mS cm -1 .
[0072] In addition to the important index of ionic conductivity, the mechanical flexibility of hydrogel electrolytes is also very important because it is an essential property of new flexible devices. The stress-strain curves of hydrogel electrolytes with different monomer ratios at room temperature are shown in Figure 2. Figure 4 As shown, the modulus of the polyA6H1 hydrogel electrolyte with high AM content is crushed by that of the polyA1H6 hydrogel electrolyte with high AMPS content. However, the strain advantage brought by the high AMPS content to the polyAH hydrogel electrolyte is not obvious. For example, the stress and strain of the polyA6H1 hydrogel electrolyte are 305.71% and 60.1 kPa, respectively, while the stress and strain of the polyA1H6 hydrogel electrolyte are only 510.24% and 7.1 kPa. Preferably, when the AM:AMPS ratio is 3:1 to 1:3, the stress of the polyAH hydrogel electrolyte is 48.9 to 11.3 kPa, and the strain is 376.36% to 480.02%.
[0073] Example 4 Mechanical Properties and Ionic Conductivity of Antifreeze Electrolyte
[0074] Considering the ionic conductivity and mechanical properties, an electrolyte with a molar ratio of AM:AMPS=3:1 was finally selected, and the antifreeze performance of the hydrogel electrolyte was studied by adding EG in different volume ratios.
[0075] Solving the freezing problem of hydrogels at low temperatures is crucial to broadening the working temperature range of hydrogels. Ethylene glycol, which is rich in hydroxyl groups, has been widely used as an antifreeze agent. This has also been studied in our previous work. Adding EG to an aqueous solution will destroy the original hydrogen bond system between water molecules and inhibit the freezing of water molecules. Here we added EG with different volume percentages as an antifreeze agent to prepare antifreeze hydrogels.
[0076] Traditional chemically cross-linked hydrogels have insufficient mechanical flexibility because their internal cross-linking points are mostly irreversible covalent bonds. The hydrogen bonds formed between EG and water are dynamically recoverable, which is very helpful in improving the flexibility of hydrogel electrolytes. The stress-strain curve of the hydrogel electrolyte at room temperature is shown in Figure 2. Figure 5 As shown in Figure 2, the ductility of the hydrogel electrolyte increases significantly with the increase of EG. For example, the strain and stress of the polyA3H1-E0 electrolyte are 376.43% and 48.89 kPa, respectively, while the polyA3H1-E 70 The strain of the electrolyte increased to 1767.27%. On the other hand, the stress decreased to 11.91 kPa. Preferably, when the EG volume ratio is 30% to 70%, the stress of the polyAH hydrogel electrolyte is 37.3 to 11.7 kPa and the strain is 728.92% to 1772.72%.
[0077] Therefore, the electrolyte has good plasticity, and its simple preparation process can easily prepare gels with complex shapes, indicating that it has great potential and can be suitable for various application scenarios.
[0078] Table 1 Ionic conductivity at different temperatures and EG contents High ionic conductivity at low temperatures is also important for the application of hydrogels at low temperatures. We then measured the conductivity of hydrogel electrolytes with different EG contents at different temperatures. The results are as follows: Figure 6 As shown in Table 1. At low temperatures, as the EG content increases, the conductivity of the hydrogel electrolyte increases first and then decreases. This is mainly because appropriate EG prevents water from freezing, but too much EG is not conducive to ion transport. The highest ionic conductivity at -40°C is 1.28 mS cm -1 , composed of polyA3H1-E 50 The electrolyte provides. More importantly, the relationship between the ionic conductivity of the electrolyte and the inverse of the absolute temperature below 0°C shows a linear relationship that obeys the Arrhenius law. polyA3H1-E 50 The activation energy of the electrolyte at low temperature is 0.307 eV, which is much smaller than that of the polyA3H1-E0 electrolyte (0.938 eV). It is well known that when the Ea value is less than 0.4 eV, the proton transport in the system follows the Grotthuss mechanism. The schematic diagram of ion transport in the hydrogel electrolyte after voltage is applied is shown in Figure 2. Figure 7 Preferably, at -40°C, when the EG volume ratio is 30% to 70%, the ionic conductivity of the polyAH hydrogel electrolyte is 0.55 to 1.28 mS cm -1 .
[0079] Example 5 Antifreeze and water retention properties of polyAH-E electrolyte
[0080] The addition of ethylene glycol not only affects the mechanical properties and conductivity of the hydrogel, but more intuitively, it affects the hydrogel's tolerance to extreme environments. Figure 8 Shown polyA3H1-E0 and polyA3H1-E 50 The low temperature tolerance of the electrolyte. The polyA3H1-E0 electrolyte freezes rapidly below 0°C and turns white. The frozen polyA3H1-E0 electrolyte becomes very fragile and loses almost all its properties (ionic conductivity is 0.13 mS cm -1 , Figure 6 ). In contrast, polyA3H1-E 50 The electrolyte remains transparent and has excellent mechanical flexibility even after being stabilized at -40°C for 5 hours, and the water molecules inside are not frozen due to the extreme low temperature. 50 Electrolytes also exhibit excellent water retention capabilities, such as Fig. 9 As shown. Two pieces of polyA3H1-E0 electrolyte and polyA3H1-E 50 After 8 days of exposure of the electrolyte to air, polyA3H1-E 50 The electrolyte still has a water retention capacity of 78.94%, but the polyA3H1-E0 electrolyte loses almost all the water in the system after 24 hours. After 8 days, the polyAH electrolyte with an ethylene glycol content of 30% to 70% has a water retention capacity of 50% to 90%.
[0081] Subsequently, differential scanning calorimetry (DSC) was used to observe the effect of different EG contents on the freezing point of the hydrogel electrolyte. Fig.10 As shown, when the EG content was 0 and 30 vol%, polyA3H1-E0 and polyA3H1-E 50 The freezing points of the electrolytes are 0°C and -21.62°C, respectively. However, when the EG content increases to 50 and 70 vol%, no endothermic peak is observed in the DSC curves, which indicates that there is no change in heat flow due to freezing.
[0082] As a strong hydrophilic molecule, EG generates hydrogen bonds after contacting with water molecules. These bonds will destroy the original three-dimensional hydrogen bond structure between water molecules and form a new and more stable EG-H2O hydrogen bond system. At the same time, it reduces the amount of free water in the solution. 50 The electrolyte exhibited excellent antifreeze properties and good water retention.
[0083] Example 6 Application of antifreeze electrolyte to supercapacitor (SC)
[0084] Assembly of organic hydrogel electrolyte-based supercapacitors (SCs)
[0085] First, 80 mg of AC, 10 mg of conductive carbon black, and 10 mg of PVDF (polyvinylidene fluoride) were ground and added with an appropriate amount of NMP to form a uniform dispersion. The dispersion was then evenly applied to a carbon cloth and placed in a vacuum oven at 180 ° C for 24 hours to obtain an AC electrode. The mass of active material on each electrode was recorded.
[0086] Two AC electrodes loaded with the same mass of active materials were taken and covered on both sides of a PolyAH-E hydrogel electrolyte to prepare a supercapacitor. In the PolyAH-E hydrogel electrolyte, AM:AMPS=3:1, and the volume ratio of EG was 50%.
[0087] Then, a few drops of electrolyte precursor solution were added to the electrodes on both sides of the capacitor to wet the electrodes. The total thickness of the prepared capacitor was about 0.9 mm, of which the thickness of the electrolyte was about 0.3 mm. The assembled SC was sealed with waterproof tape to prevent the evaporation of water in the device for subsequent electrochemical testing.
[0088] Given that polyA3H1-E 50 The electrolyte has excellent comprehensive performance, polyA3H1-E 50 The electrolyte was assembled into a supercapacitor to further study its electrochemical performance. Two carbon cloths with the same activated carbon mass were tightly attached to the polyA3H1-E 50 On both sides of the electrolyte, a "sandwich" structure supercapacitor is formed. First, a small amount of precursor solution is dripped on the two electrodes of the capacitor to fully soak the two electrodes of the SC, and then the SC is simply encapsulated with waterproof tape and relevant electrochemical tests are performed. Fig.11 As shown, the total thickness of the prepared capacitor is about 0.9 mm, while the thickness of the electrolyte is about 0.3 mm. It can completely replace liquid electrolytes and diaphragms to solve the leakage problem of energy storage devices.
[0089] The electrochemical window of SC is 100 mV s at room temperature. -1 The scan rate was determined by cyclic voltammetry (CV). Fig.12 ). Considering the water decomposition voltage (1.23 V), we selected a safe voltage (1 V) that almost presents a perfect rectangle as the final voltage window of SC. Therefore, the subsequent related electrochemical tests were performed based on the electrochemical window of 1 V.
[0090] First, the CV and constant current charge-discharge (GCD) curves of the SC were tested at room temperature, with the frequency swept from 10 mV s -1 To 200mVs -1 , the current density is from 0.05Ag -1 To 1Ag -1 ,like Fig.13 a and Fig.13 As shown in Figure 2b. The CV curve of SC presents a standard rectangle, and the GCD curve presents a standard triangle. Almost no voltage drop is observed in the GCD curve. When the temperature rises to 60°C, the CV and GCD curves of SC still maintain the standard rectangle and triangle, but the area of the CV curve increases slightly, and the discharge time of the GCD curve increases slightly ( Fig.13 c, d). These results show that based on polyA3H1-E 50 The SC of the electrolyte exhibits ideal double-layer capacitance behavior at both room and elevated temperatures.
[0091] Subsequently, the performance of SC at low temperatures was studied. Fig.14 a shows the CV curves of SC at different temperatures with a scan rate of 20 mV s -1 As the temperature decreases, the area of the CV curve gradually decreases. When the temperature drops to an extremely low temperature of -40°C, the SC CV curve still presents a standard rectangular shape. At the same time, the GCD curve also maintains a triangle ( Fig.14 b, 0.5Ag -1 ) All these indicate that polyA3H1-E 50 The SC of the electrolyte has good electrochemical performance at extremely low temperatures. Normally, a decrease in temperature will lead to a significant increase in the resistance of the hydrogel electrolyte, but polyA3H1-E 50 The resistance of the base SC increases only from 5.82Ω at 25℃ to 22.13Ω at -40℃ (5.08Ω at 60℃), as shown in Fig.14 c. From the low-frequency region of the EIS curve, it can be seen that the curve is almost parallel to the Y axis, which indicates that the polyA3H1-E 50 The electrolyte SC has good ion diffusion ability. It is worth noting that the ion diffusion behavior is very good even at an extremely low temperature of -40 °C. The fast ion diffusion behavior originates from the polyA3H1-E 50 The Grotthuss mechanism of protons inside the electrolyte, which is also the case for polyA3H1-E 50 One of the main reasons why the electrolyte can maintain good electrochemical performance and excellent ion conductivity at extremely low temperatures (1.28 mS cm -1 , Figure 6 ).
[0092] In addition, we also tested the rate performance of SC at an extremely low temperature of -40°C. Fig.15 As shown in the figure, the CV curve area at different scan rates and the GCD curve discharge time at different current densities show good rate relationships, while maintaining perfect rectangles and triangles, respectively. These results indicate that polyA3H1-E 50 The SCs of the electrolytes exhibit good rate performance and standard double-layer capacitance behavior at low temperatures.
[0093] In practical applications, higher voltage and higher energy density can be obtained by connecting several SCs in parallel and in series. In this work, compared with a single SC, two SCs in series showed an electrochemical window of 2V in both CV and GCD tests (twice that of a single SC); on the other hand, the current density and discharge time of two SCs in parallel were increased to twice that of a single SC ( Fig.16 a, b). Nyquist plot ( Fig.16 c) also reflects the characteristics of two SCs in series and in parallel, where the series resistance is the sum of the resistances of the two SCs, and the resistance of two SCs in parallel also follows 1 / R 总 =1 / R1+1 / R2.
Claims
1. A PolyAH-E hydrogel, characterized in that: The hydrogel is obtained by random polymerization of monomer acrylamide (AM) and anionic monomer 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS) in a mixed solution of ethylene glycol (EG) and water. In the polymerization unit, the molar ratio of AM and AMPS monomers is (6:1) to (1:6), and the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 10% to 70%.
2. The PolyAH-E hydrogel according to claim 1, characterized in that In the PolyAH-E hydrogel, the ratio of monomer mass to mixed solution volume is 1:2 to 1:
4.
3. The PolyAH-E hydrogel according to claim 1, characterized in that The volume concentration of ethylene glycol (EG) in the mixed solution of EG and water is 30% ~ 70%.
4. The PolyAH-E hydrogel according to claim 1, characterized in that The freezing point of the hydrogel electrolyte is lower than -21.62°C.
5. The PolyAH-E hydrogel according to claim 1, characterized in that The ionic conductivity of polyAH hydrogel electrolyte is 82.89 ~ 230.09 mS cm -1 , the stress is 37.3 ~11.7 kPa, and the strain is 728.92% ~ 1772.72%.
6. The PolyAH-E hydrogel according to claim 5, characterized in that The ionic conductivity of polyAH hydrogel electrolyte is 137.81 ~ 211.94 mS cm -1 .
7. The PolyAH-E hydrogel according to claim 1, characterized in that At -40 °C, when the EG volume ratio is 30% to 70%, the ionic conductivity of the polyAH hydrogel electrolyte is 0.55 to 1.28 mS cm -1 .
8. The PolyAH-E hydrogel according to claim 1, characterized in that After 8 days, the water retention capacity of polyAH electrolyte with ethylene glycol content of 30% to 70% was 50% to 90%.
9. The method for preparing the PolyAH-E hydrogel electrolyte according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, dissolving AM and AMPS monomers in an ethylene glycol aqueous solution, the molar ratio of AM and AMPS monomers is (6:1) to (1:6), the volume concentration of ethylene glycol in the mixed solution of ethylene glycol (EG) and water is 30% to 70%, and the ratio of monomer mass to mixed solution volume is 1:2 to 1:4; S2, place the solution obtained in S1 in an ice bath and stir for 0.5-1.5 h until all the monomers are dissolved; S3, adding an initiator to the solution obtained in S2, stirring in an ice bath for 20 to 40 minutes, and ultrasonically shaking for 5 to 15 minutes to remove bubbles, to obtain a precursor solution; the initiator is APS, and the amount of the initiator added is 0.5 to 1.5 wt% of the monomer mass; S4, inject the precursor solution into the mold, seal it and place it in a 30-50 °C environment for polymerization for 8-16 h.
10. The preparation method according to claim 9, characterized in that: In step S2, the solution obtained in S1 is placed in an ice bath and stirred for 0.8 to 1.2 h; in step S3, the amount of initiator added is 1 wt% of the monomer mass.
Citation Information
Patent Citations
Preparation method of hydrogel composite adsorption material, and application of hydrogel composite adsorption material in dye sewage treatment
CN104525152A
Semi-interpenetrating network electrosensitive hydrogel drawing agent, as well as preparation method and application thereof
CN111871205A